AI for Predictive Maintenance: Reducing Downtime and Enhancing Efficiency - Zeb, Shah; Lodhi, Shahrukh Khan (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The implementation of AI predictive maintenance technology by organizations results in operational alterations by providing predictive equipment data instead of traditional maintenance protocols. Artificial intelligence with machine learning technology along with IoT sensors brings organizations two distinct advantages including improved equipment prediction performance and better operations and budget management which reduces unexpected production breakdowns. Better operational performance and longer equipment durability accompany improved safety practices which the manufacturing industry alongside transportation healthcare sectors and aerospace and energy operations have noticed. The implementation of AI-based predictive maintenance meets various deployment challenges caused by initial cost expenses and contradictory data quality as well as security threats during integration of new infrastructure with existing platforms. Edge computing technology provides platforms that link digital duplicates with 5G capabilities to generate autonomous AI repair protocols. The implementation of artificial intelligence-based medical maintenance will progress from specialized practice to fundamental core industrial operations since it enhances equipment stability while decreasing operational breakdowns to achieve superior industrial outcomes in every sector.